2005
DOI: 10.1111/j.1600-0722.2005.00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for failure of glass fiber‐reinforced composite post restorations: a prospective observational clinical study

Abstract: Glass fiber-reinforced endodontic posts are considered to have favorable mechanical properties for the reconstruction of endodontically treated teeth. The aim of the present investigation was to evaluate the survival of two tapered and one parallel-sided glass fiber-reinforced endodontic post systems in teeth with different stages of hard tissue loss and to identify risk factors for restoration failure. One-hundred and forty-nine glass fiber-reinforced endodontic posts in 122 patients were followed-up for 5-56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
94
1
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(108 citation statements)
references
References 42 publications
6
94
1
5
Order By: Relevance
“…JCDP their elastic modulus is similar to that of dentin usually leading to fewer and more favorable fracture pattern as demonstrated by several in vivo [10][11][12] and in vitro studies. [13][14][15][16] Although posts are necessary to retain coronal build-up materials, they do not reinforce roots and may even weaken them through loss of radicular dentin necessitated by post space preparation, 6,17 while several studies also suggested that glass fiber posts contributed to the reinforcement and strengthening of endodontically treated teeth under full coverage crowns.…”
mentioning
confidence: 86%
“…JCDP their elastic modulus is similar to that of dentin usually leading to fewer and more favorable fracture pattern as demonstrated by several in vivo [10][11][12] and in vitro studies. [13][14][15][16] Although posts are necessary to retain coronal build-up materials, they do not reinforce roots and may even weaken them through loss of radicular dentin necessitated by post space preparation, 6,17 while several studies also suggested that glass fiber posts contributed to the reinforcement and strengthening of endodontically treated teeth under full coverage crowns.…”
mentioning
confidence: 86%
“…Bu başarısızlığın nedeninin bu dişlere etki eden kuvvetlerin, kontakların varlı-ğına rağmen, bukkal-lingual yönde olması olarak belirtilmiştir. 77 Fiber postların en sık karşılaşılan başarısızlık sebeplerinden biri de retansiyon kaybıdır ve bu restorasyonun ömrünü etkileyen en önemli faktördür. 78 Fiber postların kök kanalı içerisindeki tutuculuğu, postun tipi, şekli, uzunluğu, postun yüzey özellikleri, kullanılan yapıştırıcı ajanın tipi gibi çeşitli faktörler-den etkilenir.…”
Section: Yüksek Performansli Poli̇me R (Pekk) Post-kor Si̇stemi̇unclassified
“…After root canal treatment, teeth are structurally damaged, a large amount of tooth structure is lost, and teeth are much more weaker (2) . Previous studies have shown that the strength of the endodontically treated teeth depends not only on the remaining dentin (3) , and also on the periapical status and position of the tooth, the number of adjacent teeth, and occlusal contacts (4) . However, the prognosis of an endodontically treated tooth depends on endodontic procedures, and it is influenced by post-endodontic restoration (5) .…”
Section: Introductionmentioning
confidence: 99%